The Role of Leadership in Library Innovation and Change Management (International Journal of Food and Nutritional Sciences, 2022)
As libraries evolve in response to technological disruption, shifting user expectations, and institutional transformations, effective leadership has become crucial to guiding innovation and managing change. This article explores the pivotal role that library leaders play in fostering innovation, sustaining a culture of adaptability, and successfully navigating organizational change. Drawing on current literature, leadership theories, and illustrative case studies from academic and public libraries in India, the United States, Australia, and Kenya, this study examines strategies employed by effective leaders to implement digital technologies, reimagine services, and align libraries with broader institutional missions. The article concludes with actionable recommendations for leadership development in the library profession and emphasizes the importance of visionary, inclusive, and collaborative leadership styles in the future of librarianship.